Stock de carbono en la biomasa aérea de la parcela V del arboretum El Huayo CIEFOR Puerto Almendras, Iquitos, Perú, 2021 - Lomas Bustos, Wendy Jahaira (2022)
The study was carried out in the middle terrace forest of the Arboretum El Huayo CIEFOR Puerto Almendras, Iquitos, Loreto, Peru. The study was focused on quantifying the carbon stock in the aboveground biomass of forest species in plot V. The indirect method (non-destructive) was used to estimate the aboveground biomass and carbon stock. A forest inventory of trees with DBH greater than or equal to 10 cm was carried out, registering 699 trees, grouped into 165 species, 93 genera and 38 botanical families. The Fabaceae family was the most predominant with 14 genera, 25 species and 109 individuals; the species with the highest number of individuals were Alchornea triplinervia (78 trees). The results indicate an aboveground biomass of 258,076 tons (t) in the evaluated area, equivalent to 161,297 t/ha, and a carbon stock of 129,038 tons of carbon (tC) equivalent to 80,649 tC/ha. The species with the highest aboveground biomass and carbon stock were: Alchornea triplinervia with 25,225 t/ha and 12,612 tC/ha, Dimorphandra macrostachya with 10,788 t/ha and 5,394 tC/ha and Caryocar glabrum with 7,087t/ha and 3,543 tC/ha. The diameter class with the highest content of biomass and carbon stock was 20 to 29.99 cm DBH with 40,825 t/ha of biomass and 20,412 tC/ha of carbon. It was determined that the stock of carbon in the aboveground biomass varies significantly among the species studied, which indicates that some forest species have a greater capacity to store carbon.